2017
DOI: 10.18203/2320-1770.ijrcog20172327
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal breast milk expression at term increases postnatal lactational performance

Abstract: Background: Breast milk contains balanced nutrients for the complete growth of body and brain of neonates and infants. Breast feeding is rich in anti-infective factors and improves immune system, thus reducing the child mortality rate. Objective of present work was to study the effect of antenatal breast milk expression at term in improving lactational performance as compared to control group.Methods: The prospective, comparative study was conducted for 2 years to observe effects of antenatal expression of bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 7 publications
(10 reference statements)
0
15
0
Order By: Relevance
“…Eleven (55.0%) were published within the last 5 years (2015-2019) [21,24,[33][34][35][36][37][38][39][40][41]. Included studies originated from six countries: Australia (n = 7) [13,21,24,[33][34][35][36], New Zealand (n = 1) [42], the United Kingdom (n = 5) [20,39,[43][44][45], Sweden (n = 1) [46], United States (n = 3) [37,38,47], and India (n = 3) [16,40,41]. Three dominant research groups were identified; Forster et al [13,21], Demirci et al [37,38], and Casey et al [35,36], have each published two studies included in our review.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Eleven (55.0%) were published within the last 5 years (2015-2019) [21,24,[33][34][35][36][37][38][39][40][41]. Included studies originated from six countries: Australia (n = 7) [13,21,24,[33][34][35][36], New Zealand (n = 1) [42], the United Kingdom (n = 5) [20,39,[43][44][45], Sweden (n = 1) [46], United States (n = 3) [37,38,47], and India (n = 3) [16,40,41]. Three dominant research groups were identified; Forster et al [13,21], Demirci et al [37,38], and Casey et al [35,36], have each published two studies included in our review.…”
Section: Resultsmentioning
confidence: 99%
“…Whereas ten (50.0%) studies examined aBME practices in the general obstetrical population [16,24,34,37,40,41,[44][45][46][47], and ten studies (50.0%) reported on maternal or newborn outcomes as they related to high-risk populations including women with diabetes (n = 8) [13,20,21,33,35,36,42,43], hypertensive disorders of pregnancy (n = 1) [38], and overweight or obesity (n = 1) [39].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations